Efficiency evaluation of a novel supercapattery stack with a power electronic interface for energy storage systems - Kulsangcharoen, Ponggorn; Klumpner, Christian; Zhou, X.H.; Peng, C.; Chen, George Zheng; Rashed, Mohamed; Asher, Greg (2009)
The increase of renewable energy generation seen as the only way to ensure clean and sustainable development, is under scrutiny due to its intermittent nature and an insufficient development of com-plementary technologies such as electrical energy storage. There are quite a few energy storage devices available such as super/ultracapacitors that can address the high specific power applications compared to batteries, but have quite large size for same energy installed. Batteries on the other hand have much higher specific energy but cannot accommodate that easily the requirement to deliver quickly high power. This paper reports on the evaluation of a newly developed device, the supercapattery, that is a single device in which the core material is chemically engineered carbon nanotubes that can store similar amount of energy as a battery but release it faster.